UTEROTROPHIC RESPONSES AND MODULATION OF UTERINE GENE EXPRESSION INDUCED BY COMBINATIONS OF GENISTEIN AND COUMESTROL IN OVARIECTOMIZED MICE - NITU DEBNATH; JOGEN CHANDRA KALITA; SANKAR KUMAR GHOSH; BISHAL DHAR (The Bioscan, 2015)
Genistein and coumestrol are potent dietary phytoestrogens which interact differentially with estrogen receptors and thus mediate comparable estrogenicity. However, data on their combinatory effects in vivo are limited. We assessed individual and combined responses on uterine estrogen-sensitive endpoints and uterine gene expression in ovariectomized mice following subcutaneous treatment for 3 consecutive days, 14 d after ovariectomy. Effects on uterine wet weight, luminal epithelial cell height, stromal gland number and uterine ERα, ERβ and PR mRNA expression were determined using qRT-PCR. 17β-estradiol acted as positive control. Coumestrol singly exhibited stronger uterotrophic responses than genistein. However, combinations significantly increased uterine wet weight and luminal epithelial height. Pretreatment with ICI 182,780 revealed ER-dependent activity of the compounds. In contrast to 17β-estradiol, genistein up-regulated ERα while coumestrol up-regulated both ERα and ERβ expression. But, combination resulted in a dose-dependent mixed response, exhibiting marginal up-regulation of ERα at certain dose while significant down-regulation of both ERα and ERβ at other. Thus, endpoint specific and dose-dependent estrogenic responses and differential expression pattern of ERs and down-regulation of PR suggests that the tested compounds may potentially modify sensitivity and physiology of estrogen target organ, which may therefore play significant role in the prevention of endometrial cancer.